Dynamics of body condition score in different physiological stages of crossbred cattle and its effect on production traits at an organized farm in temperate region of Jammu and Kashmir - pattoo, raoof ahmad (Indian Journal of Dairy Science, 2017)
A study was conducted to evaluate the dynamics of body condition score in different physiological stages of crossbred cattle and its effect on production traits at Mountain Livestock Research Institute, Mansbal, SKUAST-K from September, 2014 to February, 2015. Fifty four crossbred cattle of same age and parity were randomly selected and grouped into three groups (A, B and C) on the basis of BCS. Animals having BCS of 2-3, 3-4 and >4 on 6 point scale were allotted to group A, B and C respectively. These groups were studied through seven different physiological stages viz. calving, early lactation, mid lactation, late lactation, dry period, heifer and pregnant heifer stages. BCS in all the three groups decreased significantly (P<0.05) from calving to early lactation with more decrease in group C (0.92) followed by B (0.68) and A (0.47). Group B had significantly (P<0.05) higher average daily milk yield (5.65±0.09) followed by C (4.18±0.27) and A (3.04±0.35). Higher (p<0.05) peak milk yield was recorded in Group C (10.07±0.22) followed by B (8.95±0.26) and A (7.43±0.57). BCS group A took significantly (P<0.05) more days to attain peak milk yield, first service and dry-period than other BCS groups. It is thus concluded that BCS varies significantly with different physiological status of crossbred cattle with significant decrease in early lactation. Best time to enhance the BCS is during late lactation. BCS 3-4 group is efficient in productive and reproductive traits as compared to BCS>4 and BCS 2-3 group.